2016
DOI: 10.1016/j.ijggc.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Flexible operation of CSIRO's post-combustion CO2 capture pilot plant at the AGL Loy Yang power station

Abstract: Flexible operation has the potential to significantly improve the economic viability of post-combustion CO2 capture (PCC). However, the impact of disturbances from flexible operation of the PCC process is unclear.The purpose of this study was to investigate the effects of flexible operation in a PCC pilot plant by implementing step-changes for improved dynamic data reliability. The flexible operation campaign was conducted at the CSIRO PCC pilot plant at AGL Loy Yang using monoethanolamine (MEA) absorbent. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…This confirms the buffering effect by the chemical process in terms of the response of CO 2 desorbed when the flue gas volumetric flow rate is changed. There is evidence to support this observation in previous pilot plant studies [46][47][48]. The delay in the response is partly attributed to solvent circulation time and the redistribution of liquid.…”
Section: Flue Gas Flow Rate Ramp-up and Step Changes In Reboiler Dutysupporting
confidence: 67%
See 1 more Smart Citation
“…This confirms the buffering effect by the chemical process in terms of the response of CO 2 desorbed when the flue gas volumetric flow rate is changed. There is evidence to support this observation in previous pilot plant studies [46][47][48]. The delay in the response is partly attributed to solvent circulation time and the redistribution of liquid.…”
Section: Flue Gas Flow Rate Ramp-up and Step Changes In Reboiler Dutysupporting
confidence: 67%
“…They concluded that the overall system acts as a buffer to perturbations at the plant inlet and that the coupled operation of the absorber/desorber unit led to fluctuations in the system when all parameters-flue gas and solvent mass flow rates and reboiler duty-are changed simultaneously. Bui et al [47] presented a flexible operation campaign conducted at the Commonwealth Scientific and Industrial Research Organization (CSIRO)'s PCC pilot plant in Australian Gas Light Company (AGL) Loy Yang, a brown-coal-fired power station in Australia. The generated transient data included step changes in flue gas flow rate, solvent flow rate and steam pressure.…”
mentioning
confidence: 99%
“…Instead of complex analytical model, data-driven models were developed through identification to investigate the characteristics of the PCC process in [20] and [21]. Dynamic performance of PCC unit were studied in [22] and [23] via open-loop step response tests on pilot plants, where the slow dynamic feature of the PCC process was clearly demonstrated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In summary, the implemented model and its numerical implementation enables transient simulation of a pilot-scale post-combustion capture plant and is adequate for dynamic control strategies development. As shown by Bui et al (2016), comparison to large scale plant-data covering a wide range of operating conditions is needed to ensure general dynamic validity of the model. It is especially important to compare the model to experiments coming from industrial-scale applications since postcombustion capture reached industrial deployment-stage.…”
Section: Gas Phase Equationsmentioning
confidence: 99%
“…In addition, differences in the physical properties of amines influence the mass transfer and hydraulic characteristics and therefore the dynamic behaviour of a capture plant. For example Bui et al (2016) reported that as MEA degrades, significant changes occur in their physical properties, e.g. viscosity which lead to poor liquid distribution.…”
Section: Dynamic Analysis and Control Designmentioning
confidence: 99%